The Elasticity of Taxable Labour Income in the Netherlands - Egbert L. W. Jongen; Maaike Stoel (Institute of Labor Economics (IZA), 2019)
We study the elasticity of taxable labour income in the Netherlands. We use a large and rich data set, including both financial and demographic variables, for the period 1999–2005. The 2001 tax reform generates large exogenous variation in marginal tax rates at different segments of the income distribution. For all workers, we find an elasticity of 0.10 in the short run, 1 year after the reform, rising to 0.24 in the medium to longer run, 5 years after the reform. Furthermore, we find that the elasticity is higher for higher incomes and women. Also, we find that the elasticity of taxable labour income is higher than the elasticity of (contractual) annual hours worked.
Keywords: H24; H31; J22; 330; elasticity of taxable income; hours worked; Netherlands